Menopause Representations Questionnaire: Adaptation and proposed Spanish version - Matzumura-Kasano, Juan P. (2022)
Introduction. The aging of women is a natural event called menopause, which requires its study for the various manifestations and how they influence during her life. Objective. To carry out the design and cultural adaptation of the Spanish version of the menopause representations questionnaire through validity and reliability tests. Methods. Research on the adaptation and validation design of the questionnaire, with the participation of women between 42 and 65 years of age, attended in first level health care facilities. A random sample of 230 women was used and the English version of the Menopause Representations Questionnaire was considered for the adaptation, back translation was performed, content validity through the expert judgment technique, convergent validity through Spearman’s correlation coefficient, internal consistency analysis through Cronbach’s Alpha coefficient and confirmatory factor analysis through Kaiser-Meyer-Olkin sample adequacy. Results. The mean age was 52.87 ± 6.29, the translation maintained the meaning of the original words, and there were no modifications in the evaluation of comprehension. Content validity by expert judgment showed a value of 0.79 according to Kappa coefficient. All the dimensions showed significant correlation for convergent validity, the reliability in the four dimensions ranged between 0.68 and 0.79 and a total reliability of 0.80. It was not necessary to eliminate questions and the confirmatory analysis was accepted. Conclusion. It is the first version translated into Spanish, has acceptable validity and reliability, can be used in clinical interventions and epidemiological studies, and is useful for describing experiences from a bio-psychosocial and cultural perspective.